Bi-curve and multi-patch smoothing with application to the shipyard industry (2007)
Algorithms are proposed and implemented in a commercial system which allow for the C1-continuity matching between adjacent B-spline curves and B-spline patches -- These algorithms only manipulate the positions of the control points, therefore respecting the constraint imposed by the sizes of the available commercial steel plates -- The application of the algorithms respect the initial hull partition made by the designers and therefore the number and overall shape and position of the constitutive patches remains unchanged -- Algorithms were designed and tested for smoothing the union of (a) two B-spline curves sharing a common vertex, (b) two B-spline surfaces sharing a common border, and (c) four B-spline surfaces sharing a common vertex -- For this last case, an iterative heuristic degreeof-freedom elimination algorithm was implemented -- Very satisfactory results were obtained with the application of the presented algorithms in shipyards in Spain